2002
DOI: 10.1007/3-540-45786-0_66
|View full text |Cite
|
Sign up to set email alerts
|

A Dynamic Brain Atlas

Abstract: Abstract. We describe a dynamic atlas that can be customized to an individual study subject in near-real-time. The atlas comprises 180 brain volumes each of which has been automatically segmented into grey matter, white matter and CSF, and also non-rigidly registered to the Montreal BrainWeb reference dataset providing automatic delineation of brain structures of interest. To create a dynamic atlas, the user loads a study dataset (eg: a patient) and queries the atlas database to identify similar subjects. All … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 9 publications
(5 reference statements)
0
9
0
Order By: Relevance
“…Several authors [6, 7, 8] have proposed kernel-based regression of brain images. The main distinction of the work described in this paper is that the underlying parametrization is learned from the image data.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors [6, 7, 8] have proposed kernel-based regression of brain images. The main distinction of the work described in this paper is that the underlying parametrization is learned from the image data.…”
Section: Related Workmentioning
confidence: 99%
“…Each template represents a part of the population. In a different direction, researchers proposed kernel-based regression of brain images with respect to an underlying parameter [6, 7, 8]. This yields a continuous curve in the space of brain images that estimates the conditional expectation of a brain image given the parameter value.…”
Section: Introductionmentioning
confidence: 99%
“…[9] is a probabilistic approach combining a standard EM-based segmentation [10] with a dynamic brain atlas construction [11].…”
Section: Expectation-maximisation-based Segmentation Using a Dynamic mentioning
confidence: 99%
“…Grid computing technology is a rapidly evolving field of interest and has been experiments have been undertaken in a wide range of areas such as particle physics, multi-scale modeling, computational steering, finance, defense research, drug discovery, decision-making, and collaborative design. The Grid applications for medical imaging analysis have also been reported [4,5]. It has been shown that the Grid can tackle complex problems in reasonable time scales and with convincing performance and this has further push the development of Grid technologies.…”
Section: Introductionmentioning
confidence: 97%